The first samurai : - Friday, Karl F. (John Wiley & Sons, 2008)
A portrait of Japan's first significant samurai leader and his world.Was samurai warrior Taira Masakado a quixotic megalomaniac or a hero swept up by events beyond his control? Did he really declare himself to be the "New Emperor"? Did he suffer divine retribution for his ego and ambition? Filled with insurrections, tribal uprisings, pirate disturbances, and natural disasters, this action-packed account of Masakado's insurrection offers a captivating introduction to the samurai, their role in 10th-century society, and the world outside the capital-a must-read for those interested in early Japan, samurai warfare, or the mystique of ancient warriors.